In vivo evidence that eIF3 stays bound to ribosomes elongating and terminating on short upstream ORFs to promote reinitiation - Mohammad, Mahabub Pasha; Munzarová Pondelícková, Vanda; Zeman, Jakub; Gunišová, Stanislava; Valášek, Leoš Shivaya (Nucleic acids research, 2017)
Translation reinitiation is a gene-specific translational control mechanism characterized by the ability of some short upstream ORFs to prevent recycling of the post-termination 40S subunit in order to resume scanning for reinitiation downstream. Its efficiency decreases with the increasing uORF length, or by the presence of secondary structures, suggesting that the time taken to translate a uORF is more critical than its length. This led to a hypothesis that some initiation factors needed for reinitiation are preserved on the 80S ribosome during early elongation. Here, using the GCN4 mRNA containing four short uORFs, we developed a novel in vivo RNA-protein Ni2+-pull down assay to demonstrate for the first time that one of these initiation factors is eIF3. eIF3 but not eIF2 preferentially associates with RNA segments encompassing two GCN4 reinitiation-permissive uORFs, uORF1 and uORF2, containing cis-acting 5΄ reinitiation-promoting elements (RPEs). We show that the preferred association of eIF3 with these uORFs is dependent on intact RPEs and the eIF3a/TIF32 subunit and sharply declines with the extended length of uORFs. Our data thus imply that eIF3 travels with early elongating ribosomes and that the RPEs interact with eIF3 in order to stabilize the mRNA-eIF3-40S post-termination complex to stimulate efficient reinitiation downstream.
Keywords: Ribosomes; ribozomy; malé podjednotky ribozomu eukaryotické; elongace translace peptidového řetězce; Peptide Chain Termination, Translational; Eukaryotic Initiation Factor-3; 5' Untranslated Regions; terminační kodon; Ribosome Subunits, Small, Eukaryotic; Open Reading Frames; Codon, Terminator; 5' nepřekládaná oblast; iniciace translace peptidového řetězce; Genetic Techniques; Peptide Chain Elongation, Translational; terminace translace peptidového řetězce; regulace genové exprese; Peptide Chain Initiation, Translational; Gene Expression Regulation; genetické techniky; eukaryotický iniciační faktor 3; otevřené čtecí rámce